The Methodologies of Orientalist Montgomery Watt in Studying the Prophetic Biography and Their Evaluation - bouras, miloud (El Omda in Linguistics and Discourse Analysis, 2023)
We have begun to put forth his ideas and manipulate the events of the development of Islamic history, and he relied on orientalist writings that are mostly based on distortion and forgery. It broadcasts and poisons it, all of this is but the ring of the cycles of maliciousness and envy that God told us in the Noble Qur’an.